First randomized evaluation of safety, pharmacodynamics, and pharmacokinetics of BAY 1831865, an antibody targeting coagulation factor XI and factor XIa, in healthy men. (20th May 2022) - Nowotny, Bettina; Thomas, Dirk; Schwers, Stephan; Wiegmann, Sara; Prange, Wolfgang; Yassen, Ashraf; Boxnick, Stefanie
Abstract: Background: Bleeding is a clinically significant issue with all current anticoagulants. Safer antithrombotic strategies are required. Objectives: To investigate the safety, pharmacodynamics, and pharmacokinetics of BAY 1831865, a humanized, factor XI (FXI)‐directed monoclonal antibody, after single intravenous (i.v.) or subcutaneous (s.c.) doses in healthy volunteers. Patients/Methods: In a first‐in‐human, phase I study, 70 volunteers were randomly assigned (4:1) to receive single‐dose BAY 1831865 (3.5, 7, 17, 35, 75, or 150 mg i.v. or 150 mg s.c.) or placebo. Adverse events, pharmacodynamics, and pharmacokinetics were evaluated. Results: In this study, no hemorrhage, or hypersensitivity or infusion‐/injection‐related reactions were reported. Drug‐related adverse events occurred in 3 (5.4%) of 56 volunteers; all were mild and self‐limited. Dose‐dependent prolongation of activated partial thromboplastin time (aPTT) and inhibition of FXI clotting activity was observed with BAY 1831865 i.v. (geometric mean maximum ratio‐to‐baseline: aPTT, range, 1.09–3.11 vs. 1.05 with placebo; FXI, range, 0.70–0.04 vs. 0.91 with placebo). Onset of effect was rapid after i.v. administration, with duration of effect (up to 55 days) determined by dose. BAY 1831865 s.c. had similar pharmacodynamic effects but a slower onset of action. Terminal half‐life increased continuously with increasing i.v. dose (range, 28–208 h), leading to strong and continuous increases in systemic exposure to BAY 1831865. Absolute bioavailability of BAY 1831865 s.c. was 47.2% (95% confidence interval, 30.2– 73.7). Conclusions: BAY 1831865 i.v. or s.c. was well tolerated, with no evidence of bleeding in healthy volunteers. BAY 1831865 exhibited pronounced, sustained dose‐dependent prolongation of aPTT and duration of FXI inhibition.